THE PECULIARITIES OF ORAL CAVITY ENZYME FUNCTIONING IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - J.G. Romanova; S.V. Dizik (Ukrainian Medical Stomatological Academy, 2016)
The aim of the study was to evaluate the functioning of the enzyme systems of oral cavity in women with polycystic ovarian syndrome. There was found that every fourth patient with Polycystic ovarian syndrome (PCOS) has manifestations of chronic catarrhal gingivitis. The level of the oral hygiene in both groups was comparable studies: 1,120,2 and 0,940,1 points accounting respectively. PMA index in women with PCOS was 35,3 ± 2,3%, while in the second group it was 11,1 ± 1,2%. Accordingly, the index CPITN in the patients of group was 2,90,2 points, while the second group of patients had 2,10,2 points (p <0,05). The patients with PCOS were marked and increased in the concentration of MDA to 0,130,02 mmol / L, the reduction in alkaline phosphatase activity was to 0,060,01 mkkat / L, the increasing activity of urease was to 0,080,01 and the decreasing production of lysozyme was to 113,013,6 U / l. It is established that the content of MDA correlates with the activity of lysozyme (r = 0,67), alkaline phosphatase (r = 0,67) and catalase (r = 0,73). The problems of the pathogenesis of periodontal lesions in women with polycystic ovary syndrome were discussed.